2014
DOI: 10.1371/journal.pone.0088437
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Implementing Integrated Mental Health Care: A District Level Situation Analysis from Five Low- and Middle-Income Countries

Abstract: BackgroundLittle is known about how to tailor implementation of mental health services in low- and middle-income countries (LMICs) to the diverse settings encountered within and between countries. In this paper we compare the baseline context, challenges and opportunities in districts in five LMICs (Ethiopia, India, Nepal, South Africa and Uganda) participating in the PRogramme for Improving Mental health carE (PRIME). The purpose was to inform development and implementation of a comprehensive district plan to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
293
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(303 citation statements)
references
References 33 publications
9
293
0
1
Order By: Relevance
“…Specifically, the Ministry of Social and Labour Affairs, the Ministry of Women and Children Affairs and the Ministry of Youth and Sport in Ethiopia; the National AIDS Control Organisation in India; the Ministry of Women, Children and Social Welfare, and the Ministry of Peace and Reconstruction in Nepal; the Department of Social Development in South Africa have been identified, and could be explored for strengthening collaborations. Although specialist mental health practitioners' (psychiatrists and psychologists) across PRIME countries were commonly believed to have high levels of support, general health practitioners (primary health care workers, community and voluntary health workers) were believed to have low-medium levels of support and interest due to being overburdened, which has also been widely documented [15,16,24,25]. This has important implications for integrating mental health into public health facilities, and creates opportunities for sensitising human resources for mental health, strategies of which are also well documented [20,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the Ministry of Social and Labour Affairs, the Ministry of Women and Children Affairs and the Ministry of Youth and Sport in Ethiopia; the National AIDS Control Organisation in India; the Ministry of Women, Children and Social Welfare, and the Ministry of Peace and Reconstruction in Nepal; the Department of Social Development in South Africa have been identified, and could be explored for strengthening collaborations. Although specialist mental health practitioners' (psychiatrists and psychologists) across PRIME countries were commonly believed to have high levels of support, general health practitioners (primary health care workers, community and voluntary health workers) were believed to have low-medium levels of support and interest due to being overburdened, which has also been widely documented [15,16,24,25]. This has important implications for integrating mental health into public health facilities, and creates opportunities for sensitising human resources for mental health, strategies of which are also well documented [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…PRIME's research programme consists of three phases over a 6-year period: Inception Phase, Implementation Phase and Scaling Up Phase [14]. As part of the Inception Phase, formative research was conducted including literature reviews, a situation analysis of mental health systems [15], in-depth interviews and focus group discussions with stakeholders [16] and Theory of Change (ToC) workshops [17]. During the Inception Phase, the following systematic steps were followed in order to collect the cross-country data required for qualitative content analysis of stakeholder perceptions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The needed services (Table 1) are also required long-term, since CMDs and SUDs are chronic, relapsing medical conditions. Based on the need for continued engagement with the health care system, integration of services for CMDs and SUDs along the HIV treatment cascade provides for optional clinical outcomes, is cost-effective, and impacts epidemic control of HIV infection [94,95].…”
Section: Services For Common Mental Disorders and Substance Use Disormentioning
confidence: 99%
“…Research on the integration of mental health into primary care is growing (1518) and these innovations should include attention to providing mental health services for SGBV survivors which is particularly challenging in resource-poor settings (19). Some studies have found using lay people to deliver CBT to SGBV survivors in extremely fragile settings to be effective in alleviating mental health symptoms (2022).…”
mentioning
confidence: 99%